2003
DOI: 10.1053/jhep.2003.50316
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and NASH: A pilot study of the effects of lifestyle modification and vitamin E

Abstract: There are few data evaluating plasma and/or peripheral blood monocyte cytokine concentrations/production or attempts to manipulate proinflammatory cytokines in nonalcoholic steatohepatitis (NASH). A pilot project in a general clinical research center evaluated the effects of a step 1 American Heart Association diet plus aerobic exercise with or without 800 IU of vitamin E daily on cytokine profiles and liver enzyme levels in 16 patients with biopsy-proven NASH. Biochemical assessment of liver function, lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
310
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(343 citation statements)
references
References 51 publications
14
310
1
8
Order By: Relevance
“…Many studies indicate that lifestyle modification may reduce aminotransferases and improve hepatic steatosis when measured either by ultrasound [73][74][75][76][77][78][79][80] 95 However, these early studies were inconclusive as a result of being small, largely uncontrolled and few using histology as the primary endpoint. More recent uncontrolled studies also showed an improvement in aminotransferases and hepatic steatosis on histology with lifestyle modification.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…Many studies indicate that lifestyle modification may reduce aminotransferases and improve hepatic steatosis when measured either by ultrasound [73][74][75][76][77][78][79][80] 95 However, these early studies were inconclusive as a result of being small, largely uncontrolled and few using histology as the primary endpoint. More recent uncontrolled studies also showed an improvement in aminotransferases and hepatic steatosis on histology with lifestyle modification.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…P r e v a l e n c e o f COP D a n d De t a i l s o f L i v e r Di s e a s e s tivation and mRNA stabilization (27). An elevation of the serum level of IL-8 has also been observed in patients with nonalcoholic steatohepatitis (30) and those with alcoholic liver disease (31) (1,32). It has been reported that the exhaled NO level is increased in liver cirrhosis (33,34), and the expression of pulmonary vascular NO synthase (NOS) is increased in hepatopulmonary syndrome (35)(36)(37) …”
Section: Smoking Is a Major Risk Factor For Copd And Aging Increases mentioning
confidence: 99%
“…1,2 Although the causes of NASH are not well defined and several therapies including diet, 3 antioxidants, 4 and approaches that improve insulin resistance 5 have been tried, no commonly accepted therapeutic protocol has yet been established. Recent studies have demonstrated a crucial role of angiotensin II in the pathogenesis of hepatic fibrosis, 6 and this peptide has been shown to enhance insulin resistance and tissue iron deposition.…”
Section: N Onalcoholic Steatohepatitis (Nash) Is a Dis-mentioning
confidence: 99%